2023
DOI: 10.3389/fnmol.2023.1099925
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-gated calcium channel subunit α2δ-1 in spinal dorsal horn neurons contributes to aberrant excitatory synaptic transmission and mechanical hypersensitivity after peripheral nerve injury

Abstract: Neuropathic pain, an intractable pain symptom that occurs after nerve damage, is caused by the aberrant excitability of spinal dorsal horn (SDH) neurons. Gabapentinoids, the most commonly used drugs for neuropathic pain, inhibit spinal calcium-mediated neurotransmitter release by binding to α2δ-1, a subunit of voltage-gated calcium channels, and alleviate neuropathic pain. However, the exact contribution of α2δ-1 expressed in SDH neurons to the altered synaptic transmission and mechanical hypersensitivity foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…For instance, previous studies have reported a signi cant elevation in CACNA2D1 expression in the DRG and spinal cord following peripheral nerve injury [17,18]. Moreover, ablation of Cacna2d1 mRNA alleviated mechanical hypersensitivity following nerve injury [19]. Notably, in our prior investigations, we observed a signi cant upregulation of CACNA2D1 within the TG after inferior alveolar nerve injury, resulting in trigeminal NP.…”
Section: Introductionsupporting
confidence: 53%
“…For instance, previous studies have reported a signi cant elevation in CACNA2D1 expression in the DRG and spinal cord following peripheral nerve injury [17,18]. Moreover, ablation of Cacna2d1 mRNA alleviated mechanical hypersensitivity following nerve injury [19]. Notably, in our prior investigations, we observed a signi cant upregulation of CACNA2D1 within the TG after inferior alveolar nerve injury, resulting in trigeminal NP.…”
Section: Introductionsupporting
confidence: 53%
“…Intrathecal injection of MGB in a mouse model of neuropathic pain significantly suppressed mechanical allodynia, whereas in a rat model of inflammatory pain induced by formalin, it significantly suppressed flinches ( Komatsu et al, 2021 ; Oyama et al, 2021 ). Recently, in patch clamp recordings using spinal cord slices from a mouse model of peripheral nerve injury, MGB reduced the amplitude of EPSCs evoked by electrical stimulation of the deep layer in the SDH ( Koga et al, 2023 ). In addition, nociceptive and itch information generated in the periphery enters the SDH primarily via C fibers, and these pathways often overlap ( Dhand and Aminoff, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that α2δ-1 is essential for nerve injury-induced increases in CP-AMPARs (11). Given that α2δ-1 exhibits specific expression in VGluT2-expressing excitatory neurons within the spinal cord (41), we determined the potential effect of memantine on synaptic CP-AMPARs in genetically labeled spinal VGluT2 neurons of mice subjected to spared nerve injury.…”
Section: Memantine Inhibits Mepscs In Cultured Neurons To Determine I...mentioning
confidence: 99%